Studies of electrical and optical properties of Sn doped and undoped ZnO thin films by the spray pyrolysis method - Arato Tovar, Ana María; García Montes, Saida Mayela; Castillo Rodríguez, Guadalupe Alan; Das Roy, Tushar Kanty (Universidad Autónoma de Nuevo León, 2011)
Undoped and tin (Sn) doped zinc oxide (ZnO) thin film have been deposited by spray pyrolysis method of zinc acetate and tin chloride. The concentration ratio of [Sn]/[Zn] was varied from 0-5 at %. The effect of doping Sn on physical and optical properties was studied by different techniques such as X-ray diffraction for structural characterization, SEM for thickness and morphology, UV-Vis spectroscopy for optical properties, Hall effect and photoconductivity for electrical characterization. X-ray diffraction (XRD) patterns show that the films deposited are polycrystalline with (002) plane as the preferential orientation. According to Scherrer's equation, grain size values on the films are foun between 30-45 nm with spherical shape. Optical trasmittance was about 92% in visible range for the optimum film and shows that the band gap decreases from 3.29 to 3.17 eV.